Challenges Encountered and Supports Needed by Novice Elementary Schools Principals in Indonesia - Tutik Susilowati, Sugeng Widarso (International Journal of Advanced Science and Technology, 2020)
This research aims to find out the problems faced by the novice elementary school principals in Indonesia and the needed supports. The research used a qualitative approach. The data were collected from interviews and FGDs. The participants consisted of principals of elementary schools from several provinces in Indonesia. The sampling technique used purposive random sampling. To ensure the validity of the data, credibility, transferability, dependability, and confirmability were tested. The results of the study showed the existed problems at the novice elementary school principals or challenges encountered at the beginning of their office related to the adaptation of positions, the environment, work culture, teacher conditions, facilities and infrastructure, school finance, and leadership. While the supports needed by the novice elementary school principals were a work guidebook for elementary school principals, supervisor mentoring and senior elementary school principals, and education and training.